Three indications for the existence of God in causal metaphysics - Meixner, Uwe (International journal for philosophy of religion, 2009)
With the emergence of modern physics a conflict became apparent between the Principle of Sufficient Cause and the Principle of Physical Causal Closure. Though these principles are not logically incompatible, they could no longer be considered to be both true; one of them had to be false. The present paper makes use of this seldom noticed conflict to argue on the basis of considerations of comparative rationality for the truth of causal statements that have at least some degree of philosophico-theological relevance and can be taken to indicate (not prove) the existence of God. The paper’s comparatively modest aim is to establish belief in the existence of God as a rational metaphysical option, not as a rational obligation. In its final section, enriched causal considerations lead to an indication (not proof) of God as that which guarantees the unified continuance of the physical world.